A modular self-assembly approach to functionalised β-sheet peptide hydrogel biomaterials. Issue 6 (6th January 2016) - King, Patrick J. S.; Giovanna Lizio, M.; Booth, Andrew; Collins, Richard F.; Gough, Julie E.; Miller, Aline F.; Webb, Simon J.
Abstract : Designed complementary peptides self-assembled into β-sheet fibrils under physiological conditions to give cell-compatible hydrogels. N-terminal modification of one peptide component with RGD improved fibroblast viability and attachment. Abstract : Two complementary β-sheet-forming decapeptides have been created that form binary self-repairing hydrogels upon combination of the respective free-flowing peptide solutions at pH 7 and >0.28 wt%. The component peptides showed little structure separately but formed extended β-sheet fibres upon mixing, which became entangled to produce stiff hydrogels. Microscopy revealed two major structures; thin fibrils with a twisted or helical appearance and with widths comparable to the predicted lengths of the peptides within a β-sheet, and thicker, longer, interwoven fibres that appear to comprise laterally-packed fibrils. A range of gel stiffnesses ( G ′ from 0.05 to 100 kPa) could be attained in this system by altering the assembly conditions, stiffnesses that cover the rheological properties desirable for cell culture scaffolds. Doping in a RGD-tagged component peptide at 5 mol% improved 3T3 fibroblast attachment and viability compared to hydrogel fibres without RGD functionalisation.